Rhabdomyolysis due to parainfluenza 3 virus infection: Case report and review of literature - Radhika Kolpuke; Lakshmi Shobhavat; Shakuntala Prabhu; Rekha Solomon (Wolters Kluwer Medknow Publications, 2019)
Influenza virus is the most frequently reported viral cause of rhabdomyolysis and case reports of rhabdomyolysis associated with parainfluenza virus are rare. We describe a seven month old child with Parainfluenza type 3 infection associated with rhabdomyolysis.